(untitled) (Homoeopathy for All, 2025)
Breast milk is said to be the first food to offer to baby. It is advised to breastfeed exclusively for the first six months of baby after birth. It is necessary for the growth and development as well as to build immunity of baby. Nowadays due to modern lifestyle, most of the mothers are facing problem of decreased milk production or insufficient milk production after delivery and due to this reason they are shifting to formula milks.